2020
DOI: 10.3390/ijerph17155373
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of Work Performance: Testing the Contribution of Emotional Intelligence and Burnout

Abstract: Previous research has highlighted the connection between emotional intelligence (EI) and work performance. However, the role of job burnout in this context remains relatively unexplored. This study aimed to examine the mediator role of burnout in the relationship between EI and work performance in a multioccupational sample of 1197 Spanish professionals (58.6% women). The participants completed the Wong and Law Emotional Intelligence Scale, the Maslach Burnout Inventory, and the Individual Work Performance Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 64 publications
3
27
0
1
Order By: Relevance
“…The implementation of workplace health promotion programs is advisable, as practical interventions have demonstrated a positive return on investment [ 47 , 48 ]. Furthermore, emotional skills programs could have a significant impact on individual and work outcomes [ 49 , 50 ]. Healthcare professionals, such as psychologists, should provide programs aimed at both the acquisition of healthy life skills and psychoeducation.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of workplace health promotion programs is advisable, as practical interventions have demonstrated a positive return on investment [ 47 , 48 ]. Furthermore, emotional skills programs could have a significant impact on individual and work outcomes [ 49 , 50 ]. Healthcare professionals, such as psychologists, should provide programs aimed at both the acquisition of healthy life skills and psychoeducation.…”
Section: Discussionmentioning
confidence: 99%
“…In the relationship between ED and mental health outcomes, the indirect effects of anger suppression and anger rumination have been reported [ 32 ], and the work environment interactions, such as emotional display rules, angry customers, and health and safety information, have also been reported [ 33 ]. Burnout, a known consequence of ED, showed a negative relationship with emotional intelligence [ 34 ]. In order to elucidate the mechanisms and mediators that might cause mental health outcomes, studies of more robust design are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Yusof, Zulkiffli, Padlee, and Yusof (2018) [31] looked at the association between organizational politics, employee satisfaction and turnover intention and reported a major correlation between organizational strategy, employee satisfaction and the plan to make a turnover. Sanchez-Gomez and Breso (2020) [32] found positive associations between emotional intelligence and success among Spanish professionals and argued that high-level emotional intelligence professionals reported the highest performance. Previous research has shown that success at work is highly influenced by emotions and feelings that are an integral part of human life in any sense [33] .…”
Section: Discussionmentioning
confidence: 99%